Quantitative high-resolution 7T MRI to assess longitudinal changes in articular cartilage after anterior cruciate ligament injury in a rabbit model of post-traumatic osteoarthritis. Issue 2 (June 2022) - Terracciano, Rossana; Carcamo-Bahena, Yareli; Royal, Amber Lee R.; Demarchi, Danilo; Labis, John Scott; Harris, Joshua D.; Weiner, Bradley K.; Gupta, Nakul; Filgueira, Carly S.
Abstract: Objective: To demonstrate an ultra-high field (UHF) 7 ​T delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) protocol for quantitative post-traumatic osteoarthritis (PTOA) detection and monitoring in a rabbit anterior cruciate ligament transection (ACLT) model. Design: ACL transections were performed unilaterally in 5 rabbits (33-weeks-old, 3.5 ​± ​0.5 ​kg) to induce PTOA. MRI exams were performed at 7 ​T prior to and 2, 4, 7 and 10-weeks after ACLT using a modified dGEMRIC protocol. Voxel-based T1 and T2 maps were created over manually drawn femoral cartilage ROIs from the center of the tibial plateau to the posterior meniscus. Femoral, tibial, and patellar epiphyses were harvested 10-weeks post-surgery and processed for μCT imaging and histology. Results: Quantitative analysis revealed a 35% and 39% decrease in dGEMRIC index in the medial ACLT knee compartment 7- and 10-weeks post-surgery, respectively ( p ​= ​0.009 and p ​= ​0.006) when compared to baseline. There was no significant change in the lateral ACLT compartment or in either compartment of the control knees. Visual inspection of histology confirmed PTOA in the ACLT knees. Osteophytes were found only in ACLT knees (osteophyte volume in femur: 94.53 ​± ​44.08 ​mm 3, tibia: 29.35 ​± ​13.79 ​mm 3, and patella: 3.84 ​± ​0.92 ​mm 3 ) and were significantly larger in the medial compartments of the femur than lateral ( p ​= ​0.0312). Conclusion: The dGEMRIC technique quantitatively applied at 7 ​T UHF-MRI demonstrates site-specific cartilage degeneration in a large animal PTOA model. This should encourage further investigation, with potential applications in drug and therapeutic animal trials as well as human studies.